Peningkatan Usaha Kecil Rumah Tangga Jemblem Frozen Berbahan Dasar Singkong di Kelurahan Kedung Kandang Malang: Increasing the Small Household Business of Frozen Cassava Ball in Kedung Kandang Village, Malang - Rani, Abdul; Kurniati, Rini Rahayu; Aini, Fitria Nugraha; Yulianti, Dyah Lestari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Kedung Kandang sub-district, Malang city, is one of the centers for small household businesses in the form of frozen jemblem, where this product is a traditional food made from cassava. However, these businesses still use traditional methods when processing it. This community service activity aims to help the partner businesses thereby assisting in the form of jemblem processing machines and faster and more hygienic methods for making frozen jemblem. The method of this community service activity is coordinating with partners to make cassava grinding machines and provide technical guidance regarding the use of cassava grinding machines. This activity resulted in the partners receiving assistance in the form of a cassava grinding machine which the partners could experience directly. Mitra feels that having this cassava grinding machine can speed up the production process and increase the sales turnover of frozen jemblem. Apart from that, with the cassava grinding machine, the frozen jemblem production process becomes more hygienic.